Regular Voluntary Exercise Potentiates Interleukin-1β and Interleukin-18 Secretion by Increasing Caspase-1 Expression in Murine Macrophages - Ken Shirato; Kazuhiko Imaizumi; Takuya Sakurai; Junetsu Ogasawara; Hideki Ohno; Takako Kizaki (Hindawi Limited, 2017)
Moderate-intensity regular exercise improves proinflammatory responses of lipopolysaccharide- (LPS-) stimulated macrophages. However, intracellular events that mediate the beneficial effects of exercise were unclear. This study aimed to clarify the mechanism by which regular voluntary exercise (VE) improves proinflammatory cytokine production by macrophages challenged with LPS. Peritoneal macrophages from VE mice secreted considerably higher amounts of interleukin- (IL-) 1β and IL-18 than did cells from sedentary control (SC) mice in the presence and absence of LPS, although tumor necrosis factor-α and IL-10 secretion were comparable between both groups. The mRNA levels of these cytokines increased significantly in response to LPS; similar levels were noted in macrophages from both SC and VE mice. Moreover, LPS evoked similar levels of degradation of inhibitor of κB (IκB) α and phosphorylation of IκB kinase β, c-Jun N-terminal kinase, and p38 in macrophages from SC and VE mice. These results indicate that the increased IL-1β and IL-18 secretion in VE mice are regulated posttranscriptionally. On the other hand, macrophages from VE mice showed higher amounts of caspase-1 protein than did cells from SC mice. These results suggest that regular VE potentiates IL-1β and IL-18 secretion in LPS-challenged macrophages by increasing caspase-1 levels.